The psychological interface between the coach-created motivational climate and the coach-athlete relationship in team sports - Olympiou, A.; Jowett, S.; Duda, J. L. (The Sport Psychologist, 2008)
The study`s objective was to investigate the motivational significance of the coachathlete relationship in team sports. 591 athletes completed the Perceived Motivational Climate in Sport Questionnaire (Newton, Duda, & Yin, 2000) to assess perceptions of the coach-created motivational climate and two Coach-Athlete Relationship Questionnaires to assess direct perceptions (Jowett & Ntoumanis, 2004) and meta-perceptions (Jowett, in press) of the relationship quality. Canonical correlation analyses revealed that the perceived task-involving features of the coaching climate, in which role importance, co-operation, and improvement are emphasized, were associated w th experiencing higher levels of closeness, commitment, and complementarity with the coach. Perceptions of the ego-involving features of the coach-created environment which emphasizes punitive responses to mistakes, rivalry, and unequal recognition were associated with lower levels of perceived closeness, commitment, and complementarity with the coach. These results support the notion that the coach-athlete relationship has implications for the motivation of athletes participating in team sports.